Comparative Analysis of Microscopy, Leishmanin Skin Test (LST), and Direct Agglutination Test (DAT) for the Diagnosis of Human Cutaneous Leishmaniasis - Mohammad Hamedanipour; Mohammad Barati; Zahra Mirabedini; Mehdi Mohebali; Alireza Latifi; Zahra Kakooie (Iranian Journal of Parasitology, 2025)
Background: Cutaneous Leishmaniasis (CL) is a highly infectious parasitic disease in Iran. Although various diagnostic methods are available, identifying a sensitive and specific approach remains essential for effective treatment and disease management. We aimed to compare microscopy, the Leishmanin Skin Test (LST), and the Direct Agglutination Test (DAT) for diagnosis of human CL. Methods: Fifty samples were obtained from clinically suspected CL cases. The results of conventional methods, including microscopy, the LST, and the DAT, were then compared among these samples. For microscopical examination considered a gold standard, smears were stained with Giemsa 10% and then examined for the observation of amastigote forms for the LST, 0.1 ml of standard Leishmanin solution was intradermally injected into positive patients, and then indurations were measured after 48-72 hours; an induration of ≥5 mm was considered positive. Additionally, anti-Leishmania antibodies were detected using DAT on positive collected serum samples. Results: Out of 50 samples collected from individuals suspected of CL, 66% (33/50) of them showed positive results using microscopic examination. Among these 33 patients diagnosed with CL, 9% (3/33) tested positive in the LST, and only 1 (3%) patient showed specific antibodies against   Leishmania using DAT. Conclusion: The microscopy method appears to be more suitable for diagnosing CL. However, there is a clear need for additional diagnostic methods with more validity for CL.